On the number of solutions of the Neumann problem for the ordinary second order differential equation - Rachůnková, Irena (Annales Mathematicae Silesianae, 1993)
We have found conditions for the nonlinearity f which are sufficient for the existence of at least two solutions to the Neumann problem for the equation u" + f(t,u,u') = s.